Life cycle informed restoration: Engineering settlement substrate material characteristics and structural complexity for reef formation. Issue 10 (8th August 2021) - Temmink, Ralph J. M.; Angelini, Christine; Fivash, Gregory S.; Swart, Laura; Nouta, Reinder; Teunis, Malenthe; Lengkeek, Wouter; Didderen, Karin; Lamers, Leon P. M.; Bouma, Tjeerd J.; van der Heide, Tjisse
Abstract: Ecosystems are degrading world‐wide, with severe ecological and economic consequences. Restoration is becoming an important tool to regain ecosystem services and preserve biodiversity. However, in harsh ecosystems dominated by habitat‐modifying organisms, restoration is often expensive and failure prone. Establishment of such habitat modifiers often hinges on self‐facilitation feedbacks generated by traits that emerge when individuals aggregate, causing density‐ or patch size‐dependent establishment thresholds. To overcome these thresholds, adult or juvenile habitat‐forming species are often transplanted in clumped designs, or stress‐mitigating structures are deployed. However, current restoration approaches focus on introducing or facilitating a single life stage, while many habitat modifiers experience multiple bottlenecks throughout their life as they transition through sequential life stages. Here, we define and experimentally test 'life cycle informed restoration', a restoration concept that focuses on overcoming multiple bottlenecks throughout the target species' lifetime. To provide proof of concept, and show its general applicability, we carried out complementary experiments in intertidal soft‐sediment systems in Florida and the Netherlands where oysters and mussels act as reef‐building habitat modifiers. We used biodegradable structures designed to facilitate bivalve reef recovery by both stimulating settlement with hard and fibrous substrates and post‐settlement survival by reducing predation. Our trans‐Atlantic experiments demonstrate that these structures enabled bivalve reef formation by: (a) facilitating larval recruitment via species‐specific settlement substrates, and (b) enhancing post‐settlement survival by lowering predation. In the Netherlands, structures with coir rope most strongly facilitated mussels by providing fibrous settlement substrate, and predation‐lowering spatially complex hard attachment substrate. In Florida, oysters were greatly facilitated by hard substrates, while coir rope proved unbeneficial. Synthesis and applications . Our findings demonstrate that artificial biodegradable reefs can enhance bivalve reef restoration across the Atlantic by mimicking emergent traits that ameliorate multiple bottlenecks over the reef‐forming organism' life cycle. This highlights the potential of our approach as a cost‐effective and practical tool for nature managers to restore systems dominated by habitat modifiers whose natural recovery is hampered by multiple life stage‐dependent bottlenecks. Therefore, investment in understanding how to achieve life cycle informed restoration on larger scales and whether the method it is applicable to restore other ecosystems is now required. Abstract : Our findings demonstrate that artificial biodegradable reefs can enhance bivalve reef restoration across the Atlantic by mimicking emergent traits that ameliorate multiple bottlenecks over the reef‐forming organism' life cycle. This highlights the potential of our approach as a cost‐effective and practical tool for nature managers to restore systems dominated by habitat modifiers whose natural recovery is hampered by multiple life stage‐dependent bottlenecks. Therefore, investment in understanding how to achieve life cycle informed restoration on larger scales and whether the method it is applicable to restore other ecosystems is now required.